Competition for access provision: Infrastructure upgrades with spillovers - Noriaki Matsushima; Keizo Mizuno (International Telecommunications Society (ITS), 2014)
We examine a game of competition with access provision in which service quality is endogenously determined through infrastructure upgrades with spillovers. There are two types of equilibria in the free competition regime. In particular, voluntary access provision with an access charge higher than access cost occurs in equilibrium, irrespective of the degree of spillover and the investment cost. However, foreclosure also occurs in equilibrium when the degree of spillover is small and the investment cost is low. We also show that, when voluntary access provision occurs in equilibrium, access regulation is socially desirable only if the degree of spillover is small and the investment cost is high. On the contrary, access regulation is socially desirable in the broader range of investment cost under foreclosure than under voluntary access provision.
Keywords: L43; L51; L96; 330; access provision; infrastructure upgrades; foreclosure